The Old Testament speaks ; v. 2 God's Word for a former generation explained for today's people - Fleming, Donald C. (Kowloon, Hong Kong Living Books for All, 1980)
Contents : v.2 : Leviticus, Numbers, Deuteronomy.
Brethren writer. Donated by the author.
Keywords: Bible. O.T. -- introductions